Activity of lenvatinib plus everolimus combination in a heavily pretreated patient with papillary renal cell carcinoma: a case report. Issue 6 (December 2020) - Zielli, Teresa; Gnetti, Letizia; Buti, Sebastiano
Background: Papillary renal cell carcinoma (pRCC) represents the second most common histologic subtype of renal cell carcinoma and comprises 2 subtypes. Prognosis for type 2 is associated with poor clinical outcome. Current guidelines are based on phase II trials, phase III trials in patients with clear cell histology, or retrospective data. Case description: To our knowledge, we describe for the first time a case of a patient with heavily pretreated metastatic pRCC who benefited from the combination of lenvatinib plus everolimus for more than 2 years. Conclusion: According to immunohistologic and biological findings in our patient both on primary tumor and liver metastasis, we hypothesize that selected patients with metastatic pRCC, progressed to standard/available treatments (including angiogenic drugs, mTOR inhibitors, and immunotherapy) and dissociated response to everolimus, could benefit from adding lenvatinib to everolimus.